Shouting and providing: Forms of exchange in the drinking accounts of young Australians. (16th June 2016) - Murphy, Dean A.; Hart, Aaron; Moore, David
Abstract: Introduction and Aims: Australian health promotion campaigns encourage people to manage their alcohol consumption by avoiding involvement in a form of round drinking known as 'shouting'. We consider this individualist advice in light of our analysis of the social relations established by young people through collective drinking, in which we conceptualise friends, family and work colleagues as participants in complex networks of exchange. Design and Methods: Data were gathered during in‐depth, semistructured interviews and ethnographic fieldwork conducted in a socioeconomically disadvantaged outer suburb of Melbourne, Australia. The interview sample comprised nine men and seven women of diverse ethnic backgrounds, with a median age of 21 years. Results: We identified two types of exchange—'shouting' and 'providing'—enacted by round drinking and other collective drinking practices. 'Shouting' is a form of balanced reciprocity in which participants take turns buying drinks for all others in the group. It is an immediate, direct exchange of alcoholic gifts that are equivalent in value. 'Providing' is characterised by indirect reciprocity in which the social aspects of the transaction are emphasised over the value of the goods exchanged. In addition to risking social exclusion, rejecting this form of collective drinking may also risk rejecting the other resources exchanged in this form of sharing, such as food, transport and accommodation. Discussion and Conclusions: Exchanges of alcoholic gifts complicate the straightforward application of individualist health promotion advice. Social relations need to be taken into account when designing health promotion interventions that seek to reduce alcohol‐related harm. [Murphy DA, Hart A, Moore D. Shouting and providing: Forms of exchange in the drinking accounts of young Australians. Drug Alcohol Rev 2017;36:442‐448]